2022
DOI: 10.1021/acsmedchemlett.1c00645
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Novel EGFR PROTACs Targeting Del19/T790M/C797S Mutation

Abstract: The tertiary epidermal growth factor receptor (EGFR) C797S mutation predominates in the acquired mutational resistance in cancer patients to third-generation EGFR inhibitors. Small-molecule inhibitors targeting the EGFR C797S mutation have been developed with good efficiency. However, these compounds may still induce new EGFR mutations to evade the inhibition pathway. One EGFR protein degrader based on an allosteric inhibitor has shown some benefits of degrading the EGFR L858R/T790M/C797S triple mutant. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Another contribution to improve IMP-targeted degradation could come from understanding the mechanisms that lead to the actual degradation of the POI in more detail. Many reports have demonstrated the involvement of the proteasome in the degradation of IMPs, ,,,,, while others have shown that the endolysosomal system is required. ,, Others have instead suggested that TPD involves the cooperation of the autophagic-lysosomal system and the UPS together, , though this could be induced by the inhibition of the proteasome, which can switch from a proteasome-dependent pathway to a lysosomal-dependent protein degradation pathway. , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another contribution to improve IMP-targeted degradation could come from understanding the mechanisms that lead to the actual degradation of the POI in more detail. Many reports have demonstrated the involvement of the proteasome in the degradation of IMPs, ,,,,, while others have shown that the endolysosomal system is required. ,, Others have instead suggested that TPD involves the cooperation of the autophagic-lysosomal system and the UPS together, , though this could be induced by the inhibition of the proteasome, which can switch from a proteasome-dependent pathway to a lysosomal-dependent protein degradation pathway. , …”
Section: Discussionmentioning
confidence: 99%
“…23,25,46 instead suggested that TPD involves the cooperation of the autophagic-lysosomal system and the UPS together, 37,42 though this could be induced by the inhibition of the proteasome, which can switch from a proteasome-dependent pathway to a lysosomal-dependent protein degradation pathway. 76,77 As targets, each membrane-associated protein presents unique properties, such as its endogenous turnover and trafficking kinetics, and its susceptibility to be internalized, which do not hinge on the technology applied. On the other hand, TPD strategies differ in the E3 employed, its endogenous levels, turnover, and stoichiometry with the target.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Compound 29 was obtained as a white solid (20 mg, yield 89%). 1 (37). Compound 37 was synthesized following the standard procedure for preparing compound 21 from intermediates 88 (11.5 mg, 0.02 mmol) and 90d (10.9 mg, 0.02 mmol, 1.0 equiv).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Notably, Gray’s group also developed an allosteric inhibitor-derived EGFR degrader, 12 (DDC-01-163), which potently degraded mutant EGFRs without affecting WT EGFRs and inhibited the proliferation of L858R/T790M mutant Ba/F3 cells and osimertinib-resistant Ba/F3 cells harboring L858R/T790M/C797S or L858R/T790M/L718Q triple mutations . Very recently, Xu’s group discovered another allosteric EGFR inhibitor-derived VHL-recruiting degrader, 13 (compound 6h ), which potently depleted EGFRs with Del19/T790M/C797S triple mutations in Ba/F3 cells . Interestingly, among these previously developed EGFR PROTAC degraders, only compound 4 , which was based on the EGFR and HER2 dual inhibitor lapatinib, was reported to induce WT EGFR degradation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation